Synergistically enhanced stability of laccase immobilized on synthesized silver nanoparticles with water-soluble polymers - Cunha, M. N. M. (2017)
Silver nanoparticles (AgNPs) were synthesized by citrate reduction method in the presence of polymers, poly(ethylene glycol) (PEG), poly(vinyl alcohol) (PVA) and chitosan, used as stabilizing agents, and an oxidoreductase enzyme, laccase (Lac), with the goal of expanding the NPs antimicrobial action. AgNPs were characterized by UV-vis spectrometry, dynamic light scattering and transmission electron microscopy. As protecting agents, PEG and PVA promoted the formation of spherical uniformly-shaped, small-sized, monodispersed AgNPs (≈20nm). High Mw polymers were established as most effective in producing small-sized NPs. Chitosan's viscosity led to the formation of aggregates. Despite the decrease in Lac activity registered for the hybrid formulation, AgNPs-polymer-Lac, a significant augment in stability over time (up to 13days, at 50°C) was observed. This novel formulation displays improved synergistic performance over AgNPs-Lac or polymer-Lac conjugates, since in the former the Lac activity becomes residual at the end of 3days. By enabling many ionic interactions, chitosan restricted the mass transfer between Lac and substrate and, thus, inhibited the enzymatic activity. These hybrid nanocomposites made up of inorganic NPs, organic polymers and immobilized antimicrobial oxidoreductive enzymes represent a new class of materials with improved synergistic performance. Moreover, the Lac and the AgNPs different antimicrobial action, both in time and mechanism, may also constitute a new alternative to reduce the probability of developing resistance-associated mutations.